2022
DOI: 10.3390/plants11151966
|View full text |Cite
|
Sign up to set email alerts
|

Pisum sativum Response to Nitrate as Affected by Rhizobium leguminosarum-Derived Signals

Abstract: Legumes are suitable for the development of sustainable agroecosystems because of their ability to use atmospheric N2 through symbiotic nitrogen fixation (SNF). However, a basic NO3− input is necessary before SNF takes place to ensure successful seedling establishment. Since Rhizobia not only induce nodulation but also affect root branching by stimulating the development of lateral roots, and NO3− as a signal also modulates root system architecture, we investigated whether Rhizobium-derived signals interfere i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…PsNPF7.1 is specifically and very strongly expressed in nodules ( Figure 2 , [ 13 ]). In a recent study, we investigated whether Rhizobium -derived signals interfere with nitrate signaling in P. sativum [ 49 ]. It appeared that PsNPF7.1 expression was induced in 12-day-old seedlings only in the presence of Rhizobium .…”
Section: Npfs Playing a Role In Nodule Functioningmentioning
confidence: 99%
“…PsNPF7.1 is specifically and very strongly expressed in nodules ( Figure 2 , [ 13 ]). In a recent study, we investigated whether Rhizobium -derived signals interfere with nitrate signaling in P. sativum [ 49 ]. It appeared that PsNPF7.1 expression was induced in 12-day-old seedlings only in the presence of Rhizobium .…”
Section: Npfs Playing a Role In Nodule Functioningmentioning
confidence: 99%
“…PsNPF7.1 is specifically and very strongly expressed in nodules (Table 1, Alves-Carvalho et al, 2015). In a recent study, we investigated whether Rhizobium-derived signals interfere with nitrate signaling in P. sativum [47]. It appeared that PsNPF7.1 expression was induced in 12-day-old seedlings only in the presence of Rhizobium.…”
Section: Npfs Playing a Role In Nodule Functioningmentioning
confidence: 99%
“…Fe deficiency can influence both the legume host and the rhizobia individually, or it can directly affect their interaction Dixon and Kahn 2004). It has been observed that Rhizobium leguminosarum is a prevalent type of rhizobia capable of forming nitrogen-fixing nodules on pea roots (Boeglin et al 2022).…”
Section: Introductionmentioning
confidence: 99%